Consumer Problems in Terms of Consumer Protection in Review of Transportation Law Regulations - Pajri Arifpadilah (Journal of Law, Politic and Humanities, 2024)
This research is motivated by the interest to understand the legal aspects in the context of transportation, especially related to delays in goods and passengers. In the context of Indonesian law, Law No. 8 Year 1999 is the basis for determining the responsibility of the shipper for the delay of goods. The purpose of this research is to investigate and analyze these aspects using a normative juridical approach. The method used involves secondary data collection through literature study, as well as constructive analysis of the data that has been processed. The results show that there are still many cases of delayed goods in Indonesia, and Law No. 8 Year 1999 positions the shipper as the party responsible for this. However, in the context of passenger delays, the settlement can vary depending on the case at hand, with the possibility of a refund as one of the settlement options. This research contributes to the understanding of the relevant aspects of transportation law in Indonesia.